RIBONUCLEIC ACID AND PROTEIN SYNTHESIS IN MITOTIC HELA CELLS - Johnson, Terry C. (The Rockefeller University Press, 1965)
HeLa cells arrested in mitosis were obtained in large numbers, with only very slight interphase cell contamination, by employing the agitation method of Terasima and Tolmach, and Robbins and Marcus. Protein synthesis and RNA synthesis were almost completely suppressed in mitotic cells. Active polyribosomes were nearly absent in mitotic cells as compared with interphase cells treated in the same way. Cell-free protein synthesis and RNA polymerase activity were also greatly depressed in extracts of metaphase cells. The deoxyribonucleoprotein (DNP) of condensed chromosomes from mitotic cells was less efficient as a template for Escherichia coli RNA polymerase than was DNP from interphase cells, although isolated DNA from both sources was equally active as a primer. Despite very poor endogenous amino acid incorporation by extracts of metaphase cells, polyuridylate stimulated phenylalanine incorporation by a larger factor in mitotic cell extracts than it did in interphase cell extracts. These results suggest that RNA synthesis is suppressed in mitotic cells because the condensed chromosomes cannot act as a template, and that protein synthesis is depressed at least in part because messenger RNA becomes unavailable to ribosomes. This conclusion was supported by the demonstration that cells arrested in metaphase supported multiplication of normal yields of poliovirus, thereby showing that the mitotic cell is capable of considerable synthesis of RNA and protein.